PENGARUH MOTIVASI KERJA, KOMPETENSI, DAN STRES KERJATERHADAP KINERJA KARYAWAN PADA PT. BPR LENGAYANG KABUPATEN PESISIR SELATAN - Restina Wahyuni Putri; Henryanto Abaharis (LP2M Universitas Bina Bangsa, 2024)
The purpose of this research is to examine the influence of work motivation, competency and work stress variables on employee performance at PT. BPR Lengayang pesisir selatan regency. This research method uses quantitative methods. Data was collected through distributing questionnaires to 40 respondents using total sampling techniques, and respondent data was processed using SPPS. The results of the research show that work motivation, competence and work stress have a positive and significant effect on employee performance at PT. BPR Lengayang Pesisir Selatan Regency